Sempervirine inhibits proliferation, invasion and metastasis of ovarian cancer cells and induces ultrastructural changes in vivo - Danni Chen; Yan Tan; Tingting Chen; Qin Wang; Yan Yan; Xiaoya Zhao; Zhongxiao Zhang; Jin Qiu; Jian Zhang (Journal of Ovarian Research)
Abstract Ovarian cancer is one of the deadliest gynecological malignancies due to its late diagnosis and easy recurrence. Therefore, it is urgent to develop novel therapeutics for ovarian cancer treatment. In this study, we evaluated the anti-ovarian cancer effects of sempervirine in vitro and in vivo. CCK8 assays showed that sempervirine dose-dependently inhibited the proliferation of SKOV3 ovarian cancer cells. Transwell assays demonstrated that sempervirine significantly suppressed the invasion and metastasis of SKOV3 cells. Furthermore, in an orthotopic ovarian cancer mouse model, sempervirine dramatically inhibited tumor growth and induced pathological changes in tumor tissues, including poor development of tumor mucosa, collagen deposition, endoplasmic reticulum damage, mitochondrial swelling and vacuolar degeneration, which were similar to the positive control 5-Fu. Mechanistic studies revealed that sempervirine decreased the expression of proteins related to apelin signaling pathway. In conclusion, our results demonstrate the potent anti-ovarian cancer effects of sempervirine both in vitro and in vivo. Sempervirine may repress ovarian cancer by down-regulating apelin signaling pathway. Our study suggests that sempervirine is a promising therapeutic agent against ovarian cancer.